THE IMPACT OF STRATEGIC AWARENESS IN RISK REDUCTION IN IRAQI INSURANCE COMPANIES - Manar Iyad Faraj; Aradan Hatem Khudair (Scholar Express Journals, 2022)
The research aims to determine the impact of strategic awareness of its dimensions of (diagnosis, evaluation, assimilation, response, and human element) in reducing the risks of insurance companies in their dimensions (identifying and analyzing risk, controlling and reviewing risks, facing risks, risks of financial performance) and the research was applied in a company The Iraqi insurance was formulated the research problem through several questions centered on the nature of the influence between the variables of the study and the degree of arrangement of these dimensions according to its importance and priorities. The analysis was done according to the descriptive approach and the analytical approach, and in light of this, the questionnaire was approved as a major tool in collecting data from the research methodology, as the number of members of the sample reached (64) people, who are from the administrative levels (higher, middle and executive) in the Iraqi Insurance Company, and data and reports have also been relied upon Financial for years (2015-2021) in explaining the results as well as conducting oral interviews with its officials. The data was analyzed by relying on the statistical program (SPSS-V26) and the (Excel) program in calculating the computational medium, standard deviation and relative importance. The research was also reached in a group of conclusions, the most important of which was a relationship of moral impact between strategic awareness of its dimensions and the dangers of insurance companies in its dimensions, and this is an indication of the company's management awareness to adopt strategic awareness in reducing the risks of insurance companies)
Keywords: strategic awareness; diagnosis; evaluation; understanding